The discourse manifestations of analytic, functional-analytic, and experiential language activities for intermediate to advanced learners of English - Brokensha, Susan Iris (University of the Free State, 2016)
This study has two principal aims. First, the descriptive aim is to describe the patterns of discourse that characterize three language teaching styles referred to by Allen (1987) in his variable focus curriculum scheme as structural-analytic (Type A), functional-analytic (Type B), and non-analytic (Type C) teaching, showing that these patterns differ significantly because they are the product of distinct speech exchange systems. The justification for this study is that, although Allen (1983; 1987; 1989) has described the features of Type A, Type B, and Type C teaching at length, few data are available on how these styles are reflected in actual classroom practices and processes. Moreover, although Allen et at. {1984) have developed a coding scheme which they refer to as the COLT procedure to distinguish between analytic and experiential language activities, it does not document the verbal exchanges characteristic of analytic teaching. Secondly, the applied linguistic aim is to show how the findings of the analyses conducted in this study may be used to improve aspects of teacher training as well as materials design and evaluation. As these aims indicate, the study of classroom discourse is not regarded as an end in itself, but as a means of promoting teachers' awareness of classroom processes so that they can make informed decisions in the language classroom. In order to achieve these aims, three corpuses of classroom data are analysed either in terms of Sacks, Schegloff and Jefferson's (1974) rule system for tum-taking in natural conversation, or in terms of McHoul's (1978) recursive rule system for classroom discourse. Due to the limitations of the Conversation Analysis perspective, aspects of the Discourse Analysis perspective of the Birmingham school (Sinclair and Coulthard, 1975) are used in the analyses. These analyses show that the discourse patterns that occur in Type A, Type B, and Type C language activities differ significantly because they are founded either on (i) a pre-allocated system of turn-taking, (ii) a Jocal-allocational system of turn-taking, or (iii) a combination of Jocal-allocational and pre-allocational means. Finally, the implications of the findings for teacher training as well as for materials design and evaluation are discussed, and, at the same time, future areas of research are briefly outlined.
Keywords: English language -- Discourse analysis; English language -- Study and teaching (Higher); Foreign speakers; Second language acquisition; Dissertation (M.A. (English)) - University of the Orange Free State, 1997